Blogging and online friendships : the role of self-disclosure and perceived reciprocity. - Goh, Hui Yi. (2008)
This study looks at how the need for affiliation, self-disclosure, and perceived reciprocity of blog writers, more commonly known as bloggers, affect the online friendships they have with their readers. Focusing on one subset of blog types, this study examines personal blogs where a high degree of self-disclosure is likely to take place. An international sample of personal blog writers (n = 416) completed an online survey that measured need for affiliation and both quantitative and qualitative aspects of self-disclosure, perceived reciprocity, and online friendships. Information on the bloggers? demographics and online behaviors was also obtained. Of the 416 respondents, 259 had made online friendships and 157 had not. Bloggers who have not made any online friendships tend to be younger, have higher need for affiliation, and have been blogging for a shorter period of time. Regression analyses reveal that need for affiliation leads to more self-disclosure, but more self-disclosure does not affect online friendships. Instead, amount of online friendships is predicted by amount of perceived reciprocity. In terms of quality, more intimacy and honesty of self-disclosure lead to more perceived reciprocity with those characteristics. Similarly, more intimacy and honesty in perceived reciprocity lead to higher degrees of intimacy and trust in online friendships. While the degree of intimacy of self-disclosure predicts intimacy in online friendships, honesty of self-disclosure has no effect on trust in online friendships. Path models indicate that more intimacy in any part of the online communication is likely to positively affect online friendships, but honesty in self-disclosure only leads to honest reciprocal disclosure, which then generates greater trust in online friendships. The theoretical and practical implications of the findings are discussed